VDR in salivary gland homeostasis and cancer. Issue 199 (May 2020) - DeSantis, Kara A.; Robilotto, Samantha L.; Matson, Mark; Kotb, Noor M.; Lapierre, Cathryn M.; Minhas, Zenab; Leder, Alana A.; Abdul, Khushbakht; Facteau, Emily M.; Welsh, JoEllen
Highlights: VDR is expressed in ductal epithelium of human and mouse salivary gland. VDR is down regulated during salivary cancer progression. Cultured salivary cells express VDR and respond to 1, 25-dihydroxyvitamin D. 1, 25D induces cell cycle arrest and alters progenitor and differentiation markers in cultured salivary cells. Abstract: The vitamin D receptor (VDR) and its ligand 1, 25(OH)2 D3 (1, 25D) impact differentiation and exert anti-tumor effects in many tissues, but its role in salivary gland has yet to be defined. Using immunohistochemistry (IHC), we have detected strong VDR expression in murine and human salivary gland ducts. Compared to normal gland, VDR protein expression was retained in differentiated human pleomorphic adenoma (PA) but was undetectable in undifferentiated PA and in carcinomas, suggesting deregulation of VDR during salivary cancer progression. To gain insight into the potential role of VDR in salivary cancer, we assessed the effects of vitamin D in vivo and in vitro . Despite the presence of VDR in salivary gland, chronic dietary vitamin D restriction did not alter morphology of the salivary epithelium in C57/Bl6 mice. The localization of VDR in ductal epithelium prompted us to examine the effects of 1, 25D in an established cell line (mSGc) derived from normal murine submandibular gland (SMG). This previously characterized cell line consists of multiple stem, progenitor and differentiated cell types as determined by mutually exclusive cellular expression of basal, ductal and myoepithelial markers. We demonstrated VDR expression and regulation of VDR target genes Vdr and Postn by 1, 25D in mSGc, indicating functional ligand-mediated transcriptional activity. The effect of VDR signaling on epithelial differentiation markers was assessed by qPCR and IHC in mSGc cells treated with 1, 25D. We found that 1, 25D reduced mRNA expression of the basal cell progenitor marker keratin 5 (K5) and increased expression of the differentiated ductal cell marker keratin 7 (K7). Further, we found that 1, 25D significantly decreased the number of proliferating cells, including proliferating K5 + cells. Characterization of cell cycle by Muse cytometry indicated 1, 25D treatment decreased cells in S, G2, and M phase. The inhibition of K5 + cell proliferation by 1, 25D is of particular interest because K5 + basal cells contribute to a wide variety of salivary tumor types. Our studies suggest that 1, 25D alters cancer-relevant progenitor and differentiation markers in the salivary gland.